Evaluasi Kinerja Dan Seleksi Peternak Mitra Pada CV Anugerah Sentosa Abadi (ARSA) - arif febryanto; abdul basith; eko ruddy cahyadi (IPB University, 2016)
The research has aims (1) to analyze selection assessment and performace evaluation of broiler chicken farmers in supply chain partnership collaboration and (2) to analyze the best partners and the most influential criteria in partner selection. The study held at CV. Anugerah Sentosa Abadi (ARSA), Bogor. We applied Analytical Hierarchi Process to develop model of partner selection and performance evaluation. The results showed that farmer personality is the highest priority criteria for partner recruitment selection with the importance weight 0.698 while Feed Convertion Ratio (FCR) is the highest priority for performance evaluation weighted 0.413. The personality criteria is mainly determined by honesty and integrity with weighted 0.433. We found that The best farmers are ranked as follows Suherman (0.454), Supendi (0.310), Makmur Bersama (0.166) dan Ebet (0.070). The results can be used by CV ARSA to review selection policy of new partner farmers and reward-punishment policy of existing partner farmers.